1977
DOI: 10.1530/jrf.0.0510111
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gonadotrophin and androgen concentrations in a freemartin ewe and its male sibling

Abstract: Investigations of plasma gonadotrophin concentrations in intact ewes have shown that, in general, LH concentrations are low and fairly stable whereas FSH levels, which are much higher, may fluctuate from 15 ng to over 100 ng FSH/ml (Salamonsen et al., 1973). However, this apparent independence of the tonic levels of plasma LH and FSH is replaced by a close association of surges of both hormones at oestrus or when provoked by oestrogen, LH-RH, or progesterone-implant removal (Reeves et al.In marked contrast, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(26 reference statements)
2
1
0
Order By: Relevance
“…The results of the present study demonstrate the presence of significant quantities of testosterone in the circulation of ovine freemartins, thereby confirming earlier reports from small numbers of animals (Saba et al, 1977;Braun et al, 1983;Bosu and Basrur, 1984;Kenny et al, 1992). These results, together with the presence of 3β-hydroxysteroid dehydrogenase within the interstitial-like tissue of the gonads , indicate that the gonad is the likely source of the steroid, whereas the much lower concentrations of testosterone in undifferentiated-type compared with maletype freemartins makes an extra-gonadal (for example, adrenal) source improbable.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study demonstrate the presence of significant quantities of testosterone in the circulation of ovine freemartins, thereby confirming earlier reports from small numbers of animals (Saba et al, 1977;Braun et al, 1983;Bosu and Basrur, 1984;Kenny et al, 1992). These results, together with the presence of 3β-hydroxysteroid dehydrogenase within the interstitial-like tissue of the gonads , indicate that the gonad is the likely source of the steroid, whereas the much lower concentrations of testosterone in undifferentiated-type compared with maletype freemartins makes an extra-gonadal (for example, adrenal) source improbable.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies of freemartin ewes support the present findings that peripheral concentrations of LH and FSH are very much higher than in intact animals, with a pattern of pulsatility that resembles that of castrated males (Saba et al, 1977;Dobson and Davies, 1989;Spedding and Dobson, 1989). Wilkes et al (1978) reported that peripheral LH concentrations of freemartins were higher than in ovariectomized ewes and, in the present study, LH concentrations in freemartins were higher than in castrated males.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation